MOLECULAR CHARACTERIZATION OF RICE (ORYZA SATIVA L.) GENOTYPES RESISTANT TO MOISTURE STRESS - DIPALI A. PATEL,; D. A. PATEL,; SUDESHNA CHAKRABORTY,; DHARNA J. PARMAR,; N. J. JADAV, (The Bioscan, 2014)
RAPD and SSR analysis of 26 genotypes of rice were performed; where RAPD and SSR with 15 and 10 primers amplified a total of 268 and 99 fragments respectively. The dendrogram generated through the study revealed that upland varieties clustered together in cluster A whereas transplanted in cluster B. The varieties with maximum similarity with other genotypes could be used as parents in hybridization programme, to generate maximum variability in segregating generation and increase scope of isolating desirable recombinants.